2010
DOI: 10.1017/s1755254011000109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high altitude and exercise on plasma erythropoietin in equids

Abstract: To help resolve the mechanistic bases for haematological adaptations (, 28% increase in red blood cell volume) of equids to high altitude (3800 m, barometric pressure P b , 487 mm Hg) and exercise, plasma erythropoietin concentration ([EPO]) was measured at rest and following exercise in six, moderately fit equids (four Arabians, one Quarter Horse and one Shetland Pony; four females and two males; age 9.0^4.5 years (mean^SD)).[EPO] was measured on 2 days at 225 m (i.e. , sea level; P b , 743 mm Hg), over the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
4
0
3
Order By: Relevance
“…Erythropoietin (EPO) is a peptide hormone produced by the kidneys in response to hypoxia sensed by receptors of the renal vasculature. Recently, it has been reported that acute exercise does not induce an increase of EPO in normal horses, neither in horses performing at altitude [81]. With pronounced effects of both central and peripheral control of cardiovascular function [82,83].…”
Section: Cardiovascular Homeostasis Fluid and Electrolyte Balance The Vasoactive Hormonesmentioning
confidence: 99%
“…Erythropoietin (EPO) is a peptide hormone produced by the kidneys in response to hypoxia sensed by receptors of the renal vasculature. Recently, it has been reported that acute exercise does not induce an increase of EPO in normal horses, neither in horses performing at altitude [81]. With pronounced effects of both central and peripheral control of cardiovascular function [82,83].…”
Section: Cardiovascular Homeostasis Fluid and Electrolyte Balance The Vasoactive Hormonesmentioning
confidence: 99%
“…McKeever (2002) concluiu que os equinos possuem uma habilidade inata para tolerar alterações agudas induzidas pelo exercício e altitude. Posteriormente, McKeever et al (2010) observaram que a exposição dos equinos a altas altitudes aumentou a concentração de EPO em 387% no primeiro dia. No entanto, 12 h mais tarde no segundo dia a EPO retornou aos valores normais pré-altitude.…”
Section: Resultsunclassified
“…Horses have an exceptionally high capacity to utilise oxygen, and move their blood volume across the pulmonary circulation, a feature accompanied by a marked exercise induced arterial hypoxemia (Fenger et al, 2000). Additionally, horses store one third to one half of their red blood cell mass in their spleen, which likely contributes to their high aerobic capacity (McKeever et al, 2010b). Horses also fail to respond to a move to altitude with a sustained EPO response, such as is seen in other species (McKeever et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, horses store one third to one half of their red blood cell mass in their spleen, which likely contributes to their high aerobic capacity (McKeever et al, 2010b). Horses also fail to respond to a move to altitude with a sustained EPO response, such as is seen in other species (McKeever et al, 2010b). We did not measure HIF in this study, but horses with heaves are able to respond to hypoxia with an increase in HIF (Toussaint et al, 2012), and equine dermal cells are able to respond to Co with an increase in HIF (Deschene et al, 2012), so it is likely that the lack of an EPO response to Co shown in other studies and confirmed here is related to an attenuated response of the horse to HIF rather than a lack of HIF response.…”
Section: Discussionmentioning
confidence: 99%